2009
DOI: 10.1111/j.1365-2435.2008.01470.x
|View full text |Cite
|
Sign up to set email alerts
|

Alarm cues experienced by cane toad tadpoles affect post‐metamorphic morphology and chemical defences

Abstract: Summary1. In many anuran species, larvae modify their developmental trajectories and behaviour in response to chemical cues that predict predator risk. Recent reviews highlight a dearth of studies on delayed (post-metamorphic) consequences of larval experience. 2. We raised cane toad ( Bufo marinus ) tadpoles either under control conditions or in the presence of non-lethal predator cues (crushed conspecifics). 3. Exposure to these chemical cues massively reduced size at metamorphosis, as predicted by theory. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
102
2
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(115 citation statements)
references
References 89 publications
2
102
2
5
Order By: Relevance
“…Chivers & Smith 1998;Ferrari et al 2007;Shabani et al 2008) and induced defences (Schoeppner & Relyea 2005;Laforsch & Beccara 2006;Hagman et al 2009). Most studies on effects of alarm cues are restricted to juveniles or adults, with effects on early embryonic development virtually unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Chivers & Smith 1998;Ferrari et al 2007;Shabani et al 2008) and induced defences (Schoeppner & Relyea 2005;Laforsch & Beccara 2006;Hagman et al 2009). Most studies on effects of alarm cues are restricted to juveniles or adults, with effects on early embryonic development virtually unknown.…”
Section: Introductionmentioning
confidence: 99%
“…So, when we collected infected tadpoles from the field, only the larger animals that were able to survive infection were left. In any case, even if tadpoles can cope sufficiently with chronic infections to resume growth and development, it is likely that infection by Bd delays metamorphosis and could have negative carryover effects on adult fitness (Wilbur & Collins 1973, Wilbur 1980, Hagman et al 2009). Ultimately, such effects at the individual level could affect population dy namics.…”
Section: Discussionmentioning
confidence: 99%
“…However, they may pay the cost of small size at metamorphosis. 8 Our study 1 showed that it is possible to use alarm pheromones to induce shortened developmental time Despite extensive research in many fields (from trap design through to genetic manipulation), we currently lack any means of controlling populations of invasive cane toads or of reducing their ecological impact. 25 In this article I have discussed the prospective of using alarm pheromones for controlling invasive cane toads.…”
Section: Potential Ways Of Using Alarm Pheromones To Control Invasivementioning
confidence: 99%
“…n a recent paper, 1 we showed that recurrent exposure to alarm pheromones reduced development time and size at metamorphosis in larval cane toads (Bufo marinus). Subsequent measurements of post-metamorphic toads revealed larger parotoid glands relative to body size and increased amounts of bufalin (a toxic bufodienalide) in animals from the experimental treatment, suggesting increased investment in chemical defenses.…”
mentioning
confidence: 99%